2002
DOI: 10.1103/physrevb.65.172105
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric ordering in the relaxorPb(Mg1/3Nb

Abstract: Neutron scattering measurements of the lowest-energy TO phonons in the relaxor Pb(Mg 1/3 Nb 2/3 )O3 (PMN) are reported for 10 ≤ T ≤ 750 K. The soft mode, which is overdamped by the polar nanoregions below the Burns temperature T d = 620 K, surprisingly recovers below 220 K. The square of the soft mode energy (hω0) 2 increases linearly with decreasing temperature, and is consistent with the behavior of a ferroelectric soft mode. At 10 K hω0 reaches 11 meV, the same value observed in ferroelectric Pb(Zn 1/3 Nb 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
122
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(136 citation statements)
references
References 22 publications
11
122
2
Order By: Relevance
“…Phonon damping below T Burns has previously been interpreted in terms of a condensation of PNR, which impede the propagation of long-wavelength polar modes. 19,20,27 Our results on PMN-0.32PT, combined with those from PMN and PMN-0.60PT, show that this strong damping persists in both relaxor and conventional ferroelectric phases and thus is not a feature unique to relaxors. Instead, the anomalous TO damping seems to correlate directly with the disorder introduced through the extensive mixing of the Mg 2+ , Nb 5+ , and Ti 4+ cations in these compounds.…”
Section: Discussion and Summarymentioning
confidence: 77%
See 3 more Smart Citations
“…Phonon damping below T Burns has previously been interpreted in terms of a condensation of PNR, which impede the propagation of long-wavelength polar modes. 19,20,27 Our results on PMN-0.32PT, combined with those from PMN and PMN-0.60PT, show that this strong damping persists in both relaxor and conventional ferroelectric phases and thus is not a feature unique to relaxors. Instead, the anomalous TO damping seems to correlate directly with the disorder introduced through the extensive mixing of the Mg 2+ , Nb 5+ , and Ti 4+ cations in these compounds.…”
Section: Discussion and Summarymentioning
confidence: 77%
“…In conventional ferroelectrics such as PbTiO 3 ͑PT͒, neutron inelastic scattering was used to show that the condensation or softening of a zone-center, transverse optic ͑TO͒ phonon mode drives the C → T ferroelectric transition, 25 while the square of the soft-mode energy ͑ប 0 ͒ 2 varies linearly with temperature above and below the Curie point ͑T C = 763 K͒ according to the Lyddane-Sachs-Teller ͑LST͒ relationship. 26 Neutron studies of the relaxors PMN, 19,20 PZN, 27 and PZN-0.08T, 28 however, revealed notable differences with PbTiO 3 in that the corresponding TO mode softens slowly and becomes heavily damped at high temperature near T d , the well-known Burns temperature where static, polar nanoregions ͑PNRs͒ first appear. 29 The soft mode remains damped down to ϳ210 K, the temperature below which a remnant polarization can be sustained in a field-cooled state, 30 but exhibits an undamped line shape at lower tem-peratures.…”
Section: ͑Pmn-xpt͒mentioning
confidence: 99%
See 2 more Smart Citations
“…The broad anomaly of the dielectric response is reflected in the phonon spectra where a soft transverse optic mode softens and then recovers with decreasing temperature. 5 Concurrent with the recovery of the soft-optic mode, strong diffuse scattering is observed along the ͗110͘ directions, indicative of short-range ferroelectric order, which persist to low temperature. Measurements using neutron pair distribution function analysis have confirmed that at low temperatures no long-range polar order is present with a maximum of ϳ1 / 3 of the sample having polar order.…”
Section: Introductionmentioning
confidence: 99%